Impact of Precipitants on the Structure and Properties of Fe-Co-Ce Composite Catalysts. (6th April 2016) - Zhang, Yongli; Dai, Shujuan; Zhou, Yanbo; Lin, Kai
Abstract : Fe-Co-Ce composite catalysts were prepared by coprecipitation method using CO(NH2 )2, NaOH, NH4 HCO3, and NH3 ·H2 O as precipitant agents. The effects of the precipitant agents on the physicochemical properties of the Fe-Co-Ce based catalysts were investigated by SEM, TEM, BET, TG-DTA, and XRD. It was found that the precipitant agents remarkably influenced the morphology and particle size of the catalysts and affected the COD removal efficiency, decolorization rate, and pH of methyl orange for catalytic wet air oxidation (CWAO). The specific surface area of the Fe-Co-Ce composite catalysts successively decreased in the order of NH3 ·H2 O, NH4 HCO3, NaOH, and CO(NH2 )2, which correlated to an increasing particle size that increased for each catalyst. For the CWAO of a methyl orange aqueous solutions, the effects of precipitant agents NH3 ·H2 O and NaOH were superior to those of CO(NH2 )2 and NH4 HCO3 . The catalyst prepared using NH3 ·H2 O as the precipitant agent was mostly composed of Fe2 O3, CoO, and CeO2 . The COD removal efficiency of methyl orange aqueous solution for NH3 ·H2 O reached 92.9% in the catalytic wet air oxidation. Such a catalytic property was maintained for six runs.